2021
DOI: 10.3390/healthcare9091216
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Mindfulness-Based Intervention Program for Women Family Caregivers of Older Adults

Abstract: Background: The objective of this study was to analyze the effectiveness of a mindfulness-based intervention program for the promotion of well-being and health in family caregivers. Methods: The participants were 111 family women caregivers aged between 33 and 75 years old. This was a double-blinded randomized controlled trial. The mindfulness intervention program lasted 12 weeks. The experimental group underwent mindfulness and acceptance-based interventions (MABIs). The control group performed physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Result of oldest old in nursing homes from rural areas by Zhu supported our finding [29]. This could be explained by the traditional sociocultural pattern of women as caregivers and men as employees in society [30] where women had lower expectations for care services and thus were more likely to show satisfaction with the care they received [29]. The finding was inconsistent with the research results of Tobis et al, who found that there was no gender difference of unmet needs between female and male residents aged over 75 years [8].…”
Section: Discussionsupporting
confidence: 81%
“…Result of oldest old in nursing homes from rural areas by Zhu supported our finding [29]. This could be explained by the traditional sociocultural pattern of women as caregivers and men as employees in society [30] where women had lower expectations for care services and thus were more likely to show satisfaction with the care they received [29]. The finding was inconsistent with the research results of Tobis et al, who found that there was no gender difference of unmet needs between female and male residents aged over 75 years [8].…”
Section: Discussionsupporting
confidence: 81%
“…[ 39 ] Among these, we can refer to studies such as the effect of cognitive behavioral therapy on the level of anxiety, stress, and depression,[ 40 ] multidisciplinary supportive program on caregiver burden and quality of life,[ 41 ] supportive educative group intervention on caregiver burden,[ 42 ] and mindfulness-based care methods on improving mental and emotional status of family caregivers of HF patients. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%